PENGARUH RASIO LIKUIDITAS, PROFITABILITAS, SOLVABILITAS DAN HARGA SAHAM TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORT DI PERUSAHAAN SEKTOR KESEHATAN - Marrisa Andinarianti; Muhammad Noval (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
ISR as a report that is not mandatory makes this disclosure interesting to be examined and juxtaposed with financial ratios, namely liquidity, profitability, solvency and stock price ratios. This study examines these financial ratios against simultaneous and partial ISR disclosures in health sector companies listed in ISSI for the 2017-2021 period. This study applied quantitative methods and multiple linear regression, the samples in this study were selected by purposive sampling techniques. The companies gathered are 12 companies. The results of the regression analysis carried out were simultaneously and partially variable liquidity, profitability, solvency, and stock price ratios, which did not significantly affect ISR disclosure.